Strategy and tactics in the treatment of 62 patients with enteroatmospheric fistula (Revista Argentina de Cirugía, 2021)
Background: the open abdomen is a widespread therapeutic resource. However, it is associated to complications among which enteroatmospheric fistula (EAF) is of utmost importance due to its high mortality and complex management.Objective: to describe the strategy for management of EAF and secondarily to analyze the outcome after introduction of a change in the conservative local treatment specifically designed for EAF.Materials and methods: from March 2002 to November 2013, patients treated for EAF were retros- pectively analyzed. They were divided into 2 groups: Group 1 (2002-2007), treated with a vacuum therapy device (Sivaco), similarly to the rest of enterocutaneous fistulae, and Group 2 (2008-2013),treated with in a specific modality. Results of conservative and surgical treatment were described and then the two groups were statistically compared.Results: Sixty-two patients were included. Twelve cases (19.4%) healed with conservative treatment, who were statistically associated with a baseline albumin level >3 g/dL, single lesion with no visible mucosa, marginal location and initial output
Keywords: enteroatmospheric fistula; enterocutaneous fistula; open abdomen; vacuum therapy